A translucent superhydrophobic composite coating and its use in cement-based materials
Patent Information
- Application Number
- CN202410897370.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-05
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-07-05
AI Technical Summary
[0003]超疏水涂层常使用含氟有机物为涂层提供极低的低表面能,但氟元素对环境与生物有一定的危害性,同样不适合于水泥基材料构件表面
[0031]有益效果:与现有技术相比,本发明具有如下显著优点:(1)通过构建“底层-微纳米结构-表层”的复合体系,提升了复合涂层的使用效果与耐久性能;(2)原材料价格低廉,实现“无氟”环保的目标;(3)应用于水泥基表面,通过简单的刷涂与喷涂的施工方法即可构建复合超疏水涂层,操作简单,应用前景广阔。
Smart Images

Figure CN118791923B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a superhydrophobic coating material, and more particularly to a semi-transparent superhydrophobic composite coating and its application in cement-based materials. Background Technology
[0002] Cement-based materials are the most widely used building materials in the construction industry. However, due to their hydrophilic properties and numerous micropores, they are easily corroded by the external environment, thus affecting the durability of the structure. Superhydrophobic surfaces are those with a static contact angle with water greater than 150° and a roll-off angle less than 10°, possessing two fundamental characteristics: a micro-nano rough structure and low surface energy. Applying superhydrophobic coatings to the surface of cement-based materials imparts self-cleaning properties and effectively improves the durability of cement-based components.
[0003] Superhydrophobic coatings often use fluorinated organic compounds to provide extremely low surface energy, but fluorine has certain harmful effects on the environment and organisms, and is also unsuitable for the surface of cement-based material components.
[0004] Therefore, it is of great significance to prepare superhydrophobic coatings using inexpensive and environmentally friendly raw materials and to construct a robust and durable superhydrophobic composite coating. Summary of the Invention
[0005] Purpose of the invention: The first purpose of this invention is to provide a semi-transparent superhydrophobic composite coating to improve the durability of the coating; the second purpose of this invention is to provide the application of the semi-transparent superhydrophobic composite coating in cement-based materials.
[0006] Technical solution: The semi-transparent superhydrophobic composite coating of the present invention includes a base layer, a micro-nano structure layer and a surface layer, wherein the surface layer is polydimethylsiloxane.
[0007] Preferably, the concentration of the polydimethylsiloxane coating is 10~40 g / L. The concentration of polydimethylsiloxane will affect the performance of the surface layer; too low a concentration will not significantly improve the durability of the composite coating, while too high a concentration will cover the micro / nano structure layer, causing the superhydrophobicity of the composite coating to disappear.
[0008] Preferably, the coating thickness of the polydimethylsiloxane is 0.5~1.5 mm.
[0009] Preferably, the bottom layer is polyacrylate. Using polyacrylate as the bottom layer effectively improves the adhesion and crack resistance of the composite coating, and enhances the adhesion between the coating and the substrate.
[0010] Preferably, the micro / nano structure layer is a multi-scale micro / nano structure composed of modified silica at the micrometer and nanoscale.
[0011] Preferably, the modified silica is isobutyltriethoxysilane-modified silica. Using isobutyltriethoxysilane-modified nano-silica constructs a micro / nano structure with superhydrophobic properties, while using polydimethylsiloxane, which has good mechanical properties and low surface energy, as the surface layer enhances the performance and durability of the composite coating.
[0012] The method for preparing the isobutyltriethoxysilane-modified silica is as follows:
[0013] (1) Disperse nano-silica, ammonia and water in ethanol, seal and disperse to make the silica particles evenly dispersed.
[0014] (2) Add tetraethyl orthosilicate to the solution prepared in step (2), seal it, and stir the reaction at 40~50°C for 30~40 min;
[0015] (3) Add isobutyltriethoxysilane to the solution prepared in step three, seal it, and stir it at 40~50°C for 4~6 h to obtain modified nano silica solution.
[0016] Preferably, the nano-silica particles have a diameter of 10~30 nm.
[0017] Preferably, in the method for preparing isobutyltriethoxysilane-modified silica, the raw materials include, by weight: 60-65 parts of anhydrous ethanol, 20-25 parts of water, 5-10 parts of ammonia, 5-10 parts of isobutyltriethoxysilane, 1-5 parts of silica, and 1-5 parts of tetraethyl orthosilicate.
[0018] Preferably, in step (1), the dispersion method is as follows: the sealed material is placed in a magnetic stirrer and heated and stirred in a 50°C water bath at 300r / min for 10~15 min.
[0019] The application of the semi-transparent superhydrophobic composite coating described in this invention in cement-based materials.
[0020] The application method includes the following steps:
[0021] (1) Polyacrylate is diluted with solvent to obtain polyacrylate solution, and then coated on the surface of cement-based material;
[0022] (2) The polyacrylate solution coated in (1) reaches a semi-cured state, and the modified nano silica solution is coated again. After drying, a micro-nano structure is formed.
[0023] (3) Dilute polydimethylsiloxane and its curing agent in a solvent to obtain a polydimethylsiloxane solution, and finally coat it onto the micro-nano structure in step (2) to form a surface layer.
[0024] Preferably, the solvent in steps (1) and (3) is ethyl acetate.
[0025] Preferably, in step (1), the coating thickness is 0.5~2 mm.
[0026] Preferably, in step (2), the coating method is spraying, using a spray gun or sprayer with a nozzle diameter of 0.5~1.5 mm, the spraying pressure is set to 0.3~0.5 MPa, and the spraying distance is 10~20 cm.
[0027] Preferably, in step (2), the coating thickness is 0.5~2 mm.
[0028] In step (3), the coating method is one of drip coating, brush coating, spin coating and spray coating.
[0029] In the preferred step (3), 1 to 5 parts by weight of polydimethylsiloxane are added to 95 to 99 parts of ethyl acetate for dilution, and the ratio of polydimethylsiloxane to curing agent is 10:1.
[0030] Mechanism of Invention: The composite superhydrophobic coating of this invention constructs a composite system of "bottom layer - micro / nano structure - surface layer". Using polyacrylate as the bottom layer, the crack resistance of the composite coating is effectively improved, and the adhesion between the coating and the substrate is enhanced. Isobutyltriethoxysilane is used to modify nano-silica, constructing a micro / nano structure with superhydrophobic properties. Simultaneously, polydimethylsiloxane, with good mechanical properties and low surface energy, is used as the surface layer to effectively protect the stability of the micro / nano structure layer, thereby improving the performance and durability of the composite coating.
[0031] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) By constructing a composite system of “bottom layer-micro-nano structure-surface layer”, the use effect and durability of the composite coating are improved; (2) The raw materials are inexpensive, achieving the goal of “fluorine-free” environmental protection; (3) When applied to cement-based surfaces, a composite superhydrophobic coating can be constructed by a simple brushing and spraying method, which is simple to operate and has broad application prospects. Attached Figure Description
[0032] Figure 1 This is a flowchart illustrating the preparation process of the composite coating of the present invention;
[0033] Figure 2 The static water contact angle diagram of the surface of the superhydrophobic composite coating prepared in Example 1;
[0034] Figure 3 Scanning electron microscope image of the surface of the superhydrophobic composite coating prepared in Example 1;
[0035] Figure 4This is a comparison chart of the static water contact angle data of the coatings in Examples 1-3 and Comparative Examples 1-5;
[0036] Figure 5 This is a comparison chart of the static water contact angle data of the coating surfaces after UV accelerated aging tests in Examples 1-3 and Comparative Examples 1-5;
[0037] Figure 6 This is a comparison chart of the static water contact angle data of the coating surfaces after the sandpaper abrasion test in Examples 1-3;
[0038] Figure 7 This is a comparison chart of the static water contact angle data of the coating surfaces after sandpaper abrasion tests in Example 1 and Comparative Examples 1-5. Detailed Implementation
[0039] The technical solution of the present invention will be further described below with reference to the embodiments.
[0040] Example 1
[0041] The method for preparing the translucent superhydrophobic composite coating of the present invention includes the following steps:
[0042] (1) Substrate treatment: The mortar test blocks were ultrasonically cleaned and dried for later use.
[0043] (2) Preparation of polyacrylate: Weigh 20 g of polyacrylate and 4 g of ethyl acetate, mix them, and stir at high speed until uniform to obtain a polyacrylate solution.
[0044] (3) Preparation of modified silica solution: Weigh 80 g of anhydrous ethanol, 30 g of water, 10 g of ammonia and 2 g of nano silica (particle size 20 nm), mix them, seal them and place them in a magnetic stirrer and heat and stir at 300 r / min in a 50°C water bath for 10 min. Then add 2 g of tetraethyl orthosilicate to the mixed solution and heat and stir at 300 r / min in a 50°C water bath for 30 min. Then add 10 g of isobutyltriethoxysilane to the mixed solution, seal it and heat and stir at 300 r / min in a 50°C water bath for 4 h to obtain the modified nano silica solution.
[0045] (4) Preparation of polydimethylsiloxane solution: Add 2 g of polydimethylsiloxane and 2 g of curing agent to 200 g of ethyl acetate, and sonicate for 15 min until completely dispersed to obtain a uniform polydimethylsiloxane solution.
[0046] (5) The polyacrylate prepared in step (2) is uniformly brushed onto the surface of the mortar substrate with a thickness of 1 mm. It is dried at room temperature for 4 h to reach a semi-cured state. Then, the modified nano silica solution prepared in step (3) is sprayed onto the surface of the polyacrylate bottom layer with a micro-nano structure layer thickness of 1 mm. It is dried at room temperature for 12 h. The polydimethylsiloxane solution prepared in step (4) is uniformly brushed onto the surface of the "bottom layer-micro-nano structure" layer with a thickness of 1 mm. Finally, it is cured at room temperature for 12 h to obtain a semi-transparent superhydrophobic composite coating of the mortar substrate.
[0047] The surface of the coating in this embodiment was characterized by its microstructure and superhydrophobicity was tested. Scanning electron microscopy morphology images and water static contact angle diagrams were obtained, as follows: Figure 2 and 3 As shown.
[0048] Depend on Figure 2 As can be seen, this embodiment successfully created a coating surface composed of an ordered, micro-nano-scale uneven structure, with smaller protrusions distributed on top of larger ones. This multi-level rough structure of the coating surface can be filled with air, forming a superhydrophobic structure. Figure 3 Thus, water droplets do not remain on the surface in a wetting contact state and have difficulty penetrating into the micro-nano structure of the coating, making it easier for water droplets to roll on the coating surface.
[0049] Example 2
[0050] Based on Example 1, the concentration of the polydimethylsiloxane solution in step (5) is 10 g / L, the coating thickness is 1.5 mm, and the other conditions remain unchanged.
[0051] Example 3
[0052] Based on Example 1, in step (5), the concentration of the polydimethylsiloxane solution is 40 g / L, the coating thickness is 0.5 mm, and the other conditions remain unchanged.
[0053] Comparative Example 1
[0054] The preparation method of this comparative example includes the following steps:
[0055] (1) Substrate treatment: The mortar test blocks were ultrasonically cleaned and dried for later use.
[0056] (2) Preparation of polyacrylate: Weigh 20g of polyacrylate and 4g of ethyl acetate, mix them, and stir at high speed until uniform to obtain polyacrylate.
[0057] (3) The polyacrylate prepared in step (2) is uniformly brushed onto the surface of the mortar substrate and dried at room temperature for 12 hours to obtain a polyacrylate coating.
[0058] Comparative Example 2
[0059] The preparation method of this comparative example includes the following steps:
[0060] (1) Substrate treatment: The mortar test blocks were ultrasonically cleaned and dried for later use.
[0061] (2) Preparation of polyacrylate: Weigh 20g of polyacrylate and 4g of ethyl acetate, mix them, and stir at high speed until uniform to obtain polyacrylate.
[0062] (3) Preparation of modified silica solution: Weigh 80g anhydrous ethanol, 30g water, 10g ammonia and 2g nano silica, mix them, seal them and place them in a magnetic stirrer and heat and stir at 300r / min in a 50°C water bath for 10min. Then add 2g tetraethyl orthosilicate to the mixed solution and heat and stir at 300r / min in a 50°C water bath for 30min. Then add 10g isobutyltriethoxysilane to the mixed solution, seal it and heat and stir at 300r / min in a 50°C water bath for 4h to obtain modified nano silica solution.
[0063] (4) The polyacrylate prepared in step (2) is uniformly brushed onto the surface of the mortar substrate and dried at room temperature for 4 hours to reach a semi-cured state. Then, the modified nano silica solution prepared in step (3) is sprayed onto the surface of the polyacrylate substrate and dried at room temperature for 12 hours. A substrate-micro-nano structure composite coating is obtained.
[0064] Comparative Example 3
[0065] The preparation method of this comparative example includes the following steps:
[0066] (1) Substrate treatment: The mortar test blocks were ultrasonically cleaned and dried for later use.
[0067] (2) Preparation of polyacrylate: Weigh 20g of polyacrylate and 4g of ethyl acetate, mix them, and stir at high speed until uniform to obtain polyacrylate.
[0068] (3) Preparation of polydimethylsiloxane solution: Add 4g of polydimethylsiloxane and 0.4g of curing agent to 200g of ethyl acetate, and sonicate for 15min until completely dispersed to obtain a uniform polydimethylsiloxane solution.
[0069] (4) The polyacrylate prepared in step (2) is uniformly brushed onto the surface of the mortar substrate and dried at room temperature for 4 hours to reach a semi-cured state. Then, the modified polydimethylsiloxane solution prepared in step (3) is applied to the surface of the polyacrylate substrate and cured at room temperature for 12 hours to obtain a substrate-surface composite coating.
[0070] Comparative Example 4
[0071] Based on Example 1, the thickness of the polydimethylsiloxane solution brush coating in step (5) is 0.2 mm, and the other conditions remain unchanged.
[0072] Comparative Example 5
[0073] Based on Example 1, the thickness of the polydimethylsiloxane solution brush coating in step (5) is 3 mm, and the other conditions remain unchanged.
[0074] Performance Characterization
[0075] The coatings obtained in Examples 1-3 and Comparative Examples 1-5 were subjected to 48 hours of accelerated aging under ultraviolet light and 10 rounds of sandpaper abrasion tests (400-grit sandpaper, 200g load). After the tests, the static water contact angle of the coatings was measured, as shown below. Figures 4-7 As shown.
[0076] Depend on Figure 4 and 5 As can be seen, the composite coatings of Examples 1-3 exhibited good resistance to UV aging. Comparative Example 1, consisting only of the bottom layer, showed rapid aging and performance degradation after accelerated UV aging of the polyacrylate layer. Comparative Example 2, with its bottom layer and micro / nano structure coating, showed no significant change in superhydrophobicity after accelerated UV aging. Comparative Example 3, with its bottom layer and surface layer composite coating, showed decreased hydrophobicity due to the decomposition of the surface polydimethylsiloxane. However, Examples 1-3 still maintained stable superhydrophobicity because the surface polydimethylsiloxane exhibited good resistance to UV aging, effectively protecting the micro / nano structure layer.
[0077] Depend on Figure 6 It can be seen that the contact angle of Examples 1-3 decreased slowly after wear.
[0078] Depend on Figure 7 It can be seen that Comparative Example 1 only has a polyacrylate substrate and lacks superhydrophobic properties. Comparative Example 2, with its substrate-micro / nanostructure composite coating, has a micro / nanostructure layer composed of modified nano-silica, but lacks the protection of a polydimethylsiloxane surface layer, exhibiting fragile mechanical stability. In Comparative Example 3, the contact angle of the substrate-surface composite coating decreases slowly. In Comparative Example 4, when the concentration of polydimethylsiloxane in the surface layer is too low, it cannot completely cover the micro / nanostructure layer, resulting in poor protection of the composite coating. In Comparative Example 5, when the concentration of polydimethylsiloxane in the surface layer is too high, it completely covers the protrusions of the micro / nanostructure layer, failing to achieve a superhydrophobic effect.
[0079] Example 1 exhibits more stable wear resistance compared to Comparative Examples 1-3. This is because the appropriate concentration and thickness of the surface layer will precisely adhere the micro-nano structure layer, significantly improving the durability of the composite coating.
Claims
1. The application of a semi-transparent superhydrophobic composite coating in cement-based materials, characterized in that, It includes a bottom layer, a micro / nano structure layer, and a top layer. The top layer is polydimethylsiloxane; the bottom layer is polyacrylate; the micro / nano structure layer is a multi-scale micro / nano structure composed of micron-scale and nano-scale modified silica; the modified silica is isobutyltriethoxysilane-modified silica. The coating thickness of the polydimethylsiloxane is 0.5~1.5 mm; The coating thickness of the bottom layer and the micro / nano structure layer is 0.5~2mm; The method for preparing the isobutyltriethoxysilane-modified silica is as follows: (1) Disperse nano-silica, ammonia and water in anhydrous ethanol, seal and disperse to make the nano-silica particles evenly dispersed. (2) Add tetraethyl orthosilicate to the solution prepared in step (2), seal it, and stir it at 40~50℃ for 30~40 min; (3) Add isobutyltriethoxysilane to the above mixed solution, seal it, and stir the reaction at 40~50℃ for 4~6h to obtain modified silica solution.
2. The application according to claim 1, characterized in that, The concentration of the polydimethylsiloxane coating is 10~40 g / L.
3. The application according to claim 1, characterized in that, The nano-silica particles have a diameter of 10~30nm.
4. The application according to claim 1, characterized in that, In the preparation method of the isobutyltriethoxysilane modified silica, the raw materials include, by weight: 60-65 parts of anhydrous ethanol, 20-25 parts of water, 5-10 parts of ammonia, 5-10 parts of isobutyltriethoxysilane, 1-5 parts of nano silica, and 1-5 parts of tetraethyl orthosilicate.
5. The application according to claim 1, characterized in that, The application method includes the following steps: (1) Polyacrylate is diluted with solvent to obtain polyacrylate solution, and then coated on the surface of cement-based material; (2) The polyacrylate solution coated in (1) reaches a semi-cured state, and the modified silica solution is coated again. After drying, a micro-nano structure is formed. (3) Dilute polydimethylsiloxane and its curing agent in a solvent to obtain a polydimethylsiloxane solution, and finally coat it onto the micro-nano structure in step (2) to form a surface layer.
Citation Information
Patent Citations
Super-hydrophobic glass and manufacturing method thereof
CN102501477A
Super-hydrophobic coating, super-hydrophobic coating layer as well as preparation method and application of super-hydrophobic coating layer
CN109370418A
Super-hydrophobic composite coating and preparation method thereof
CN111299104A